Development and Validation of Models to Predict Pathological Outcomes of Radical Prostatectomy in Regional and National Cohorts. Issue 2 (23rd February 2022) - Ötleş, Erkin; Denton, Brian T.; Qu, Bo; Murali, Adharsh; Merdan, Selin; Auffenberg, Gregory B.; Hiller, Spencer C.; Lane, Brian R.; George, Arvin K.; Singh, Karandeep
Abstract : Purpose: Prediction models are recommended by national guidelines to support clinical decision making in prostate cancer. Existing models to predict pathological outcomes of radical prostatectomy (RP)—the Memorial Sloan Kettering (MSK) models, Partin tables, and the Briganti nomogram—have been developed using data from tertiary care centers and may not generalize well to other settings. Materials and Methods: Data from a regional cohort (Michigan Urological Surgery Improvement Collaborative [MUSIC]) were used to develop models to predict extraprostatic extension (EPE), seminal vesicle invasion (SVI), lymph node invasion (LNI), and nonorgan-confined disease (NOCD) in patients undergoing RP. The MUSIC models were compared against the MSK models, Partin tables, and Briganti nomogram (for LNI) using data from a national cohort (Surveillance, Epidemiology, and End Results [SEER] registry). Results: We identified 7, 491 eligible patients in the SEER registry. The MUSIC model had good discrimination (SEER AUC EPE: 0.77; SVI: 0.80; LNI: 0.83; NOCD: 0.77) and was well calibrated. While the MSK models had similar discrimination to the MUSIC models (SEER AUC EPE: 0.76; SVI: 0.80; LNI: 0.84; NOCD: 0.76), they overestimated the risk of EPE, LNI, and NOCD. The Partin tables had inferior discrimination (SEER AUC EPE: 0.67; SVI: 0.76; LNI: 0.69; NOCD: 0.72) as compared to other models. The Briganti LNI nomogram had an AUC of 0.81 in SEER but overestimated the risk. Conclusions: New models developed using the MUSIC registry outperformed existing models and should be considered as potential replacements for the prediction of pathological outcomes in prostate cancer.